Using the personal to critique the popular: women’s memories of 1960s youth - Mills, H (Routledge, 2016)
Popular memory depicts 1960s young adults as affluent, permissive, promiscuous, delinquent, sub- or counter-cultural rebels. But these stylised images do not reflect the lived experiences of ordinary young adults, particularly young women, in the 1960s. Using Mass Observation and oral history interviews, this article examines how women who were young adults in the 1960s remember their youths and how they negotiate the gap between popular memory and personal experience. It argues that women can readily critique the popular memory of 1960s youth where it does not match their own lived experience. The popular memory is powerful, however, and so still shapes their understanding of the experiences and concepts of youth more generally. Moreover, the way women negotiate between popular and personal memories of youth is conditioned by their attempt to create composure and by subsequent life experiences.